Μιχαήλ Ι. Μουσαίος: Ο γάμος του Μαλώνη Αντιφάτου - Πούχνερ Βάλτερ (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1984)
The drama The marriage of Malonis Antifatis (more exactly the first act of the theatrical work), is the only example of theatrical art from the region of Lycia (Livisi) on the southeast Aegean coast of Asia Minor. It is written in the local Greek dialect; its author is Michail I. Mousaios (1829-1896), one of the outstanding local scholars of the 19th century in that area, who is a characteristic representative of the «delayed enlightenment » of the Greek orthodox population of Asia Minor. His primary motive in the composition of the play was his belief that the purity of the spoken language offered unmistakable evidence of purity of the cultural origins. So the goal of one of his works, Battarismoi, a vocabulary of the Greek dialect of the region in the form of a lexicon, is firstly to describe the alienation and decadence of the spoken language in his homeland, and secondly to «improve» it, that is to purify the Greek and to eliminate the Turkish words which were in common use. The same goal is served by the theatrical work The marriage of Malonis Antifatis which plays in 1823, two years after the outbreak of the Greek revolution, and reenacts all the phases and activities of a tradi- donai engagement as well as the negotiations preparing the marriage. But the author’s interest is not a folkloristic one. It is, as he explains in the introduction, first a linguistic one, and secondly it aims at the cultural enlightenment of his compatriots. His intention is to give them an initial stimulus to purify their language and habits. The drama is characterised by an anticlerical attitude: the Orthodox priests and the great landowners (Kocabasi) try to stop any attempt at enlightenment and progress and they are responsible for the «Asiatic» decadence of the community. The Turkish words, sentences and proverbs in the text have not only the function of giving a sense of couleur locale, but they show expressively the decadence of language, culture and institutions. These are the ideological highlights of the drama, which the main figure, Prokopios, puts foreward in extended soliloquies. The drama was not written to be played on the stage. But it does not lack theatrical qualities: the dialogue between the father and mother of Malonis Antifatis is quick and vivid with stimulating turns, giving an interesting insight into folk mentality and strategies of match-making. But when Prokopios enters the stage, the style becomes more didactic, in a manner of giving lessons at school. Prokopios, who often addresses the public directly, uses the Greek «katharevousa», the purified language of scholars and literateurs in the 19th century. He, as «hieromonachos», is the idealised model of correcting language and manners as Mousaios puts it. This unique drama from the Lycian province is an important cultural document of Asia Minor both for its content — language, habits and manners, customs, mental structures, ways of life— and for what it symbolizes— the effort at enlightenment in the second half of the 19th century (when enlightenment in Greece was «démodé» for some decades). The play is a didactic manifesto against uncultivated conservatism, ignorance, and provincial backwardness, as these things are institutionalised in the class of priests and landowners. The Marriage of Antifatis is an important literary and ideological document in the history of Greek literature and, last but not least, a theatrical monument from an area without theatrical tradition.